A Review on Islamic Bank Law: A Qualitative Approach - Solihah Sari Rahayu; Anwar Adem Shikur; Dwi Ratna Kartikawati (Journal of Islamic Economics Literatures, 2023)
Islamic banking and the law issue become a topic that has been studied more and more in the last few decades. This study aims to analyze the literature related to Islamic bank law with coverage of research trends and future research directions. A total of 375 articles sourced from Scopus which were analyzed using the biblioshiny R software. The findings in this study include keywords that are often used in research, including banking, sustainable development, Malaysia, Islamic bank law and Islamism. While the authors who have the greatest contribution to this study are Scholtenz B, Peres-gladish, and Nilsson J. Finally, the latest topic trends in related research Islamic bank law are Covid-19, pandemic, ESG, and ratings.